The Neuroimmune Interplay in Joint Pain: The Role of Macrophages - Vasconcelos, Daniela P.; Jabangwe, Clive; Lamghari, Meriem; Alves, Cecília J. (Frontiers in Immunology, 2022)
Chronic pain associated with joint disorders, such as rheumatoid arthritis (RA), osteoarthritis (OA) and implant aseptic loosening (AL), is a highly debilitating symptom that impacts mobility and quality of life in affected patients. The neuroimmune crosstalk has been demonstrated to play a critical role in the onset and establishment of chronic pain conditions. Immune cells release cytokines and immune mediators that can activate and sensitize nociceptors evoking pain, through interaction with receptors in the sensory nerve terminals. On the other hand, sensory and sympathetic nerve fibers release neurotransmitters that bind to their specific receptor expressed on surface of immune cells, initiating an immunomodulatory role. Macrophages have been shown to be key players in the neuroimmune crosstalk. Moreover, macrophages constitute the dominant immune cell population in RA, OA and AL. Importantly, the targeting of macrophages can result in anti-nociceptive effects in chronic pain conditions. Therefore, the aim of this review is to discuss the nature and impact of the interaction between the inflammatory response and nerve fibers in these joint disorders regarding the genesis and maintenance of pain. The role of macrophages is highlighted. The alteration in the joint innervation pattern and the inflammatory response are also described. Additionally, the immunomodulatory role of sensory and sympathetic neurotransmitters is revised.